Desolate / Muhammad Zaidi Zainal Abidin and Muhammad Falihin Jasmi - Zainal Abidin, Muhammad Zaidi; Jasmi, Muhammad Falihin (Faculty of Art and Design, 2021)
The paper collage is inspired by the absence of gestures during the Movement Control Order (MCO). The emptiness, loneliness, and dullness of ambiance are portrayed through the top view scenery of the small jetty at the fishing village. The river shows its natural color, which is free from human activities and any pollutants. The abandoned boats tell the plight of fishermen who have to stop doing any activities to earn a living. The pandemic had changed human nature and habits whilst leaving a huge impact on the entire environment. The process of the artwork started by selecting a photo as an inspirational image that shows the real condition during the Movement Control Order (MCO). It was followed by selecting recycled papers from magazines that suit the real color of the inspirational image and was cut into a variety of small pieces. Each tiny piece is pasted carefully on the greyscale inspirational image to fill the entire space. Every process was passionately and neatly done towards producing a clean and precise artwork. All in all, the paper collage is an expression of arts during the boredom and trying to tell the audiences about the true color of the pandemic that brings both positive and negative impacts to humankind and Mother Nature. It is up to humans to face, adapt and find solutions to end this unexpected situation and continue to live.